Malaria - White, N; White, N; Pukrittayakamee, S; Hien, T; Faiz, M; Mokuolu, O; Dondorp, A; Dondorp, A (2014)
Although global morbidity and mortality have decreased substantially, malaria, a parasite infection of red blood cells, still kills roughly 2000 people per day, most of whom are children in Africa. Two factors largely account for these decreases; increased deployment of insecticide-treated bednets and increased availability of highly effective artemisinin combination treatments. In large trials, parenteral artesunate (an artemisinin derivative) reduced severe malaria mortality by 22·5% in Africa and 34·7% in Asia compared with quinine, whereas adjunctive interventions have been uniformly unsuccessful. Rapid tests have been an important addition to microscopy for malaria diagnosis. Chemopreventive strategies have been increasingly deployed in Africa, notably intermittent sulfadoxine-pyrimethamine treatment in pregnancy, and monthly amodiaquine-sulfadoxine-pyrimethamine during the rainy season months in children aged between 3 months and 5 years across the sub-Sahel. Enthusiasm for malaria elimination has resurfaced. This ambitious but laudable goal faces many challenges, including the worldwide economic downturn, difficulties in elimination of vivax malaria, development of pyrethroid resistance in some anopheline mosquitoes, and the emergence of artemisinin resistance in Plasmodium falciparum in southeast Asia. We review the epidemiology, clinical features, pathology, prevention, and treatment of malaria.